THE PARENTS’ PARTICIPATION AND STUDENTS’ BEHAVIOR IN MODULAR DISTANCE LEARNING TOWARDS THE ACADEMIC PERFORMANCE OF THE STUDENTS OF PAG-ASA NATIONAL HIGH SCHOOL - Jayson R.Salvador, Adela P.Sacay (EPRA International Journal of Research and Development (IJRD), 2023)
This study aimed to identify the level of the parents’ participation and level of the students’ behavior in accomplishing the Learning Activity Sheets and/or Modules of the modular distance learning students of Pag-asa National High School. Predominantly, this study is focused on the identified characteristics or roles of the parents and the behaviors of the students during the modular distance learning to modify the process of the school in garnering bigger percentage of Learning Activity Sheets to be retrieved from the students. The identified behavior of the modular distance learning students was also correlated to the students’ academic performance to improve and develop learning materials such as the Learning Activity Sheets and the Modules. The study utilized the descriptive-survey type of research to determine the level of the parents’ participation and students’ behavior in modular distance learning. The results of the study revealed that the level of the parents’ participation in accomplishing the Learning Activity Sheets has a verbal interpretation of Great Extent and the given situations are often done by the parents. On the other hand, the behavior of the students in accomplishing the Learning Activity Sheets, has a verbal interpretation of Great Extent and the given behavioral situations are considered often done by the learners. This study focused and limited only on the level of the parents’ participation and students’ behavior based on the perception of the learners from Grade 10 Modular Distance Learning section one (MDL 1) and to assess the relationship of the students’ behavior to their performance during the first year of the implementation of the modular distance learning. This action research will guide the parents in assisting their children to accomplish their Learning Activity sheets considering the different behaviors of their children during the time of pandemic. The results of this study will also serve as an initial move to work with the parents and other members of the schools and the community to help the learners in improving their behavior and study skills.